QATAR V. UNITED ARAB EMIRATES RACIAL DISCRIMINATION DISPUTE - Emylia Roseta; Eristiana Sari; Muhamad Rival Maulana; Joshua Aldo Tri Putra; Awan Shofa Maulana (Universitas Duta Bangsa Surakarta, 2023)
Qatar and the United Arab Emirates are the two countries that have clashed in 2017 because Qatar and the United Arab Emirates are the two countries that have clashed in 2017 because of the blockade and expulsion issues carried out by the United Arab Emirates against Qatari citizens, this is what makes the United Arab Emirates violate racial discrimination. The beginning of this problem was because the United Arab Emirates thought that Qatar had violated the 2013 Riyadh Agreement. In international law, human rights have the status of Jus Cogens which is regulated in article 53 of the 1969 Vienna Convention. So that the United Arab Emirates was reported by Qatar to the ICJ for violating racial discrimination . The two countries resolved the dispute through mediation brokered by the ICJ. From these problems, ICJ issued the International Court of Justice Decision Number 172 of 2018. This research uses a qualitative and normative juridical approach, namely by conducting research on literature reading sources and analyzing them by law. The author gets the source by searching for secondary sources, namely scientific journals that have been written by other people as a reference source of this research. This study has limitations, namely analyzing the issue of racial discrimination which is a dispute between Qatar and the United Arab Emirates. This research has a great contribution to provide learning about international disputes and their resolution to the wider community which of course has the aim of providing knowledge and insight for readers. Keywords: Racial discrimination, Jus cogens, Human Rights.